Lipoprotein(a) Levels and the Risk of Myocardial Infarction Among 7 Ethnic Groups - Paré, G; Çaku, A; McQueen, M; Anand, S; Enas, E; Clarke, R; Boffa, M; Koschinsky, M; Wang, X; Yusuf, S; Interheart Investigators (American Heart Association, 2019)
BACKGROUND:Lipoprotein(a) [Lp(a)] levels predict the risk of myocardial infarction (MI) in populations of European ancestry; however, few data are available for other ethnic groups. Furthermore, differences in isoform size distribution and the associated Lp(a) concentrations have not fully been characterized between ethnic groups. METHODS:We studied 6086 cases of first MI and 6857 controls from the INTERHEART study that were stratified by ethnicity and adjusted for age and sex. A total of 775 Africans, 4443 Chinese, 1352 Arabs, 1856 Europeans, 1469 Latin Americans, 1829 South Asians, and 1221 Southeast Asians were included in the study. Lp(a) concentration was measured in each participant using an assay that was insensitive to isoform size, with isoform size being assessed by Western blot in a subset of 4219 participants. RESULTS:Variations in Lp(a) concentrations and isoform size distributions were observed between populations, with Africans having the highest Lp(a) concentration (median=27.2 mg/dL) and smallest isoform size (median=24 kringle IV repeats). Chinese samples had the lowest concentration (median=7.8 mg/dL) and largest isoform sizes (median=28). Overall, high Lp(a) concentrations (>50 mg/dL) were associated with an increased risk of MI (odds ratio, 1.48; 95% CI, 1.32-1.67; P<0.001). The association was independent of established MI risk factors, including diabetes mellitus, smoking, high blood pressure, and apolipoprotein B and A ratio. An inverse association was observed between isoform size and Lp(a) concentration, which was consistent across ethnic groups. Larger isoforms tended to be associated with a lower risk of MI, but this relationship was not present after adjustment for concentration. Consistent with variations in Lp(a) concentration across populations, the population-attributable risk of high Lp(a) for MI varied from 0% in Africans to 9.5% in South Asians. CONCLUSIONS:Lp(a) concentration and isoform size varied markedly between ethnic groups. Higher Lp(a) concentrations were associated with an increased risk of MI and carried an especially high population burden in South Asians and Latin Americans. Isoform size was inversely associated with Lp(a) concentration, but did not significantly contribute to risk.